Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
<h2>
Answer:</h2>
C = 2πr
r = C/2π ...(1)
A = πr²
A = π(C/2π)² = πC²/4π²
A = C²/4π.
<u>Correct choice</u> - [A] A = C²/4π.
The converse of t > r is r > t
<h3>What is a converse statement?</h3>
A converse statement is determined when both the hypothesis and conclusion are reversed or interchanged.
In this condition, the hypothesis is written as the conclusion and the conclusion is changed to be the hypothesis.
If a conditional statement is written as: x → y
The converse is then written as y → x
Where;
- x is the hypothesis
- y is the conclusion
Given the expression as;
t > r
We can see that;
- The variable 't' is the hypothesis
- The variable 'r' is the conclusion
The converse will be;
r > t
Hence, the converse is r > t
Learn more about converse statement here:
brainly.com/question/3965750
#SPJ1
You basically just split it right down the middle. if the cost of something is lets say $75.58, then you would divide 75.58 by 2, which is $37.79
hope it helps!!